Functional Diversity of RNAi-Associated sRNAs in Fungi - Francisco E. Nicolás (International Journal of Molecular Sciences, 2013)
Yeast and filamentous fungi have been essential model systems for unveiling the secrets of RNA interference (RNAi). Research on these organisms has contributed to identifying general mechanisms and conserved eukaryotic RNAi machinery that can be found from fungi to mammals. The development of deep sequencing technologies has brought on the last wave of studies on RNAi in fungi, which has been focused on the identification of new types of functional small RNAs (sRNAs). These studies have discovered an unexpected diversity of sRNA, biogenesis pathways and new functions that are the focus of this review.